DEMOCRACY CAUGHT BETWEEN READINESS TO SERVE AND EAGERNESS TO DOMINATE - Menamparampil, Thomas (Asian Horizons, 2020)
Today’s political structures arise from early tribal traditions that promoted an accountable and responsible leadership, which ruled by the norms of ordinary good sense, truthfulness and happy relationship. Unfortunately, an eagerness to dominate has often warped the natural instinct in the human being to commit one’s energies for the common good. It can be held in check only by arousing a sense of responsibility in citizens and strengthening their sense of co-belonging. Today even existing democracies are in danger where global business magnates and the ruling cliques are in close alliance. Majoritarian democracies are becoming oppressive of the minorities. Institutions of democracy are being abused for the interests of the dominant groups. Truth is being marginalized. Restoration of truth and re-building of relationships based on ‘good sense’ will revive the values of responsibility and accountability. If there is the need of reform of laws and structures within democracy, there is equally need of renewal of values and healing of relationships. Awakening of the sense of co-belonging and of public responsibility is the most urgent need.